Political instability and labor market institutions - Claudio Lucifora; Simone Moriconi (Institute for the Study of Labor (IZA), 2012)
This paper investigates the relationship between political instability and labor market institutions. We develop a theoretical model in which some features of the political process, by reducing the future yields of policy interventions, induce an incumbent government to choose labor market institutions that create wage rents and divert resources from public good provision and social insurance. We test these predictions empirically using panel data for 21 OECD countries for the period 1985-2006. We find strong evidence that political turnover and political polarization - our measures of political instability - are associated with a more regulated labor market, lower unemployment benefit replacement rates, and a smaller tax wedge on labor. We show also that there are strong complementarities between different dimensions of political instability, and evaluate their impact on labour market institutions across countries.
urn:nbn:de:101:1-20120716941
Keywords: J64; J88; H11; 330; political instability; labor market institutions; unemployment; Politische Stabilität; Arbeitsmarktpolitik; Institutionalismus; Arbeitslosigkeit; OECD-Staaten